2023
DOI: 10.3390/ijms24065409
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Aspects Implicated in Dantrolene Selectivity with Respect to Ryanodine Receptor Isoforms

Abstract: Dantrolene is an intra-cellularly acting skeletal muscle relaxant used for the treatment of the rare genetic disorder, malignant hyperthermia (MH). In most cases, MH susceptibility is caused by dysfunction of the skeletal ryanodine receptor (RyR1) harboring one of nearly 230 single-point MH mutations. The therapeutic effect of dantrolene is the result of a direct inhibitory action on the RyR1 channel, thus suppressing aberrant Ca2+ release from the sarcoplasmic reticulum. Despite the almost identical dantrolen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 228 publications
0
2
0
Order By: Relevance
“…To do so, we took advantage of the selective ER Ca 2+ channel antagonists xestospongin-C (XeC, 1 μM) ( 21 ) and dantrolene (Dan, 10 μM) ( 22 ), to block IP3Rs and RyR1, respectively. Dan mainly selectively inhibits RyR1 over RyR2 ( 22 , 23 , 24 ), but the selectivity remains controversial ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…To do so, we took advantage of the selective ER Ca 2+ channel antagonists xestospongin-C (XeC, 1 μM) ( 21 ) and dantrolene (Dan, 10 μM) ( 22 ), to block IP3Rs and RyR1, respectively. Dan mainly selectively inhibits RyR1 over RyR2 ( 22 , 23 , 24 ), but the selectivity remains controversial ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that EC of the human mesenteric artery and immortalized EA.hy926 endothelial-derived cells express RyR3, whereas RyR1 and RyR2 were not detected in these cells [ 35 ]. RyR3 is known to be inhibited by dantrolene [ 36 ]. We used this compound to find out if RyRs in HUVEC are involved in the potentiation of the response to BW723C86 by CGS12066B.…”
Section: Resultsmentioning
confidence: 99%